15 Years of Research on US Employment and the Minimum Wage. (18th July 2019) - Wolfson, Paul; Belman, Dale
Abstract: Statistical analysis of the minimum wage and employment has been very active for the last quarter century, including more than 37 studies of US data since the December 2000 AER exchange involving Card, Krueger, Neumark and Wascher. In this meta‐analysis of the 37 that report results suitable for this technique, the most important finding is a considerable shift toward the origin in the 'consensus range': from the interval [−0.3, −0.1] to [−0.13, −0.07]. The minimum wage has negative employment effects, but these have become notably smaller and are largely localized to teenagers.